A simple expression for the bulk field capacity of a sloping soil horizon - Soulis, E. D.; Craig, J. R.; Fortin, V.; Liu, G. (Hydrological processes, 2011)
Field capacity is a commonly used soil parameter in surface water hydrological models, loosely defined as the moisture content of a soil after drainage. The most commonly applied expression for field capacity is defined as the remaining water in a vertical soil column subject to 1/3 atm. of pressure head. While this quantification is sufficient in some cases, the definition is not consistent with the use of bulk field capacity in calculations of lateral drainage from hillslopes, as required by some surface soil parameterizations, nor does it address additional complications arising from differences in soil texture or sample size. Here, a simple alternative expression for bulk field capacity in a sloping or vertical soil is derived directly from Richards equation with the use of the Brooks‐Corey characteristics. It is demonstrated that this expression is consistent with data acquired from vertical soil columns, but may be extended to additional situations commonly found in surface water models and land surface schemes. The calculation of bulk field capacity requires only the Brooks‐Corey pore size distribution index, soil air‐entry pressure, and hillslope length and slope, and may be considered a physically based alternative to pedotransfer function or lookup table approaches. Copyright © 2010 John Wiley & Sons Ltd and Crown in the right of Canada.